Apoptosis signaling pathways in osteoarthritis and possible protective role of melatonin. Issue 4 (24th September 2016) - Hosseinzadeh, Azam; Kamrava, Seyed Kamran; Joghataei, Mohammad Taghi; Darabi, Radbod; Shakeri‐Zadeh, Ali; Shahriari, Mansour; Reiter, Russel J.; Ghaznavi, Habib; Mehrzadi, Saeed
Abstract: Osteoarthritis (OA) is a degenerative joint disease characterized by progressive erosion of articular cartilage. As chondrocytes are the only cell type forming the articular cartilage, their gradual loss is the main cause of OA. There is a substantial body of published research that suggests reactive oxygen species (ROS) are major causative factors for chondrocyte damage and OA development. Oxidative stress elicited by ROS is capable of oxidizing and subsequently disrupting cartilage homeostasis, promoting catabolism via induction of cell death and damaging numerous components of the joint. IL‐1β and TNF‐α are crucial inflammatory factors that play pivotal roles in the pathogenesis of OA. In this process, the mitochondria are the major source of ROS production in cells, suggesting a role of mitochondrial dysfunction in this type of arthritis. This may also be promoted by inflammatory cytokines such as IL‐1β and TNF‐α which contribute to chondrocyte death. In patients with OA, the expression of endoplasmic reticulum (ER) stress‐associated molecules is positively correlated with cartilage degeneration. Melatonin and its metabolites are broad‐spectrum antioxidants and free radical scavengers which regulate a variety of molecular pathways such as inflammation, proliferation, apoptosis, and metastasis in different pathophysiological situations. Herein, we review the effects of melatonin on OA, focusing on its ability to regulate apoptotic processes and ER and mitochondrial activity. We also evaluate likely protective effects of melatonin on OA pathogenesis.